EVALUATION OF THE HOLISTIC EDUCATION BASED LEARNING PROGRAM AT THE INTEGRATED ISLAMIC HIGH SCHOOL - A. Mustika Abidin; Misykat Malik Ibrahim; St. Syamsudduha; Ilyas Ismail; Sitti Mania; Nur Syamsiah; Muh Rapi (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This study aims to evaluate the process of holistic education based learning programs at SMAIT Al-Fityan School Gowa. The research focuses on learning development, learning integration, teacher strategies, student responses, learning interactions, and the use of methods. This study employs an evaluative research design using a mixed-methods approach with an explanatory sequential design. Quantitative data collection and analysis were conducted first through the distribution of questionnaires to 30 students, followed by qualitative data collection through interviews with 3 teachers and 6 students to gain a more comprehensive understanding. The findings indicate that the evaluation of the holistic education-based learning program at SMAIT Al-Fityan School Gowa showed that 73.3% of the outcomes were at the “sufficiently achieved” or “fairly good” level. The learning process has developed students’ knowledge, attitudes, skills, and character; integrated various dimensions of holistic education namely intellectual, emotional, physical, social, and spiritual dimensions; employed varied learning strategies; created a pleasant classroom atmosphere; and strengthened student interactions. However, the implementation of the learning process still faces challenges, particularly in developing students’ skills, integrating physical aspects, and maintaining consistency in learning strategies. This study concludes that holistic education-based learning is important to implement in the classroom because it emphasizes the holistic and integrated development of students, encompassing intellectual, emotional, social, spiritual, and physical aspects. This approach views the learning process not merely as the transfer of knowledge, but as the process of forming the whole person, which takes place within specific social, cultural, and value systems.